2004
DOI: 10.1093/alcalc/agh045
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic Trials in Adolescent Alcohol Use Disorders: Opportunities and Challenges

Abstract: Medications as adjuncts to psychosocial treatments for adolescent alcohol use disorders hold the promise of improved efficacy over psychosocial treatments alone. Specific components should be included in the design and implementation of these medication studies. Included should be assessment of the developmental risks of the chosen medication, consideration of short-term effects on the clinical disorder, factors affecting compliance and retention, age-specific pharmacokinetics, and systematic safety monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 134 publications
1
10
0
Order By: Relevance
“…Although pharmacotherapy is a common adjunct to psychosocial interventions for adolescents with AUDs, limited empirical evidence is available, and developmentally tailored studies are needed. 144 For example, despite the high rates of psychiatric comorbidity among youths with alcohol and other drug problems, few behavioral or pharmacologic studies have focused on these populations. 145 Treatment outcome studies clearly indicate the disadvantage to abusing/dependent youths of concomitant axis I mental health disorders and distinctive process and context differences challenging such youths.…”
Section: Developmental Context and Traditional Treatment Effortsmentioning
confidence: 99%
“…Although pharmacotherapy is a common adjunct to psychosocial interventions for adolescents with AUDs, limited empirical evidence is available, and developmentally tailored studies are needed. 144 For example, despite the high rates of psychiatric comorbidity among youths with alcohol and other drug problems, few behavioral or pharmacologic studies have focused on these populations. 145 Treatment outcome studies clearly indicate the disadvantage to abusing/dependent youths of concomitant axis I mental health disorders and distinctive process and context differences challenging such youths.…”
Section: Developmental Context and Traditional Treatment Effortsmentioning
confidence: 99%
“…Based on a convergence of literature suggesting that age and gender are important factors to consider when developing a translational approach (Greenfield et al, 2010, Dawes and Johnson, 2004), we tested the first general hypothesis that both influence binge alcohol consumption.…”
mentioning
confidence: 99%
“…Gastrointestinal symptoms were the most common adverse event (Toren et al 2005). There are no published studies of this agent in adolescents with SUD, although Dawes and Johnson have reported successful reductions in alcohol consumption in a small open-label (n = 12) trial of ondansetron (Dawes and Johnson 2004).…”
Section: Anticraving Agentsmentioning
confidence: 99%
“…The average daily dose of 50 mg was well tolerated. However, others have reported that the 50-mg dose produces significant nausea in adolescents, requiring the use of lower doses (Dawes and Johnson 2004).…”
Section: Anticraving Agentsmentioning
confidence: 99%
See 1 more Smart Citation